Acute kidney injury and chronic kidney disease in umbilical cord blood transplant recipients - Lopedote, Paolo; Xue, Elisabetta; Chotivatanapong, Julie; Pao, Emily C.; Wychera, Chiara; Dahlberg, Ann E.; Thur, Laurel; Roberts, Laura; Baker, Kelsey; Gooley, Ted A.; Hingorani, Sangeeta; Milano, Filippo (Frontiers in Oncology, 2023)
Acute kidney injury (AKI) is a frequent early complication post hematopoietic stem cell transplant (HSCT), associated with high morbidity and mortality. We retrospectively evaluated 276 adults and children who underwent a first cord blood transplant (CBT) for hematologic malignances to identify risk factors for AKI. We also aimed to identify the impact of AKI on chronic kidney disease (CKD) and survival outcomes by one-year post-CBT. AKI was staged according to Kidney Disease Improving Global Outcomes (KDIGO) definitions. Median age was 32 years, 28% (77/276) were children (<18 years) and 129 (47%) were white. A myeloablative conditioning regimen was administered to 243 patients (88%) and 248 (90%) received cyclosporine for GVHD prophylaxis. One-hundred and eighty-six patients (72%) developed AKI by day 60 post-transplant, with 72 (28%) developing severe AKI (stage 2 and 3). In a multivariable analysis, each increase in bilirubin level of 1 mg/dL was associated with a 23% increase in the risk of severe AKI (HR 1.23, 95% CI 1.13 – 1.34, p<.0001). Conversely, systemic steroid administration appeared to be protective of severe AKI (aHR 0.36, 95% CI 0.18 – 0.72, p=.05) in a multivariable model. Two-hundred-forty-seven patients were evaluable at the one-year time point. Among those, 100 patients (40%) developed CKD one-year post-CBT. Severe AKI was associated with a higher hazard of non-relapse mortality (adjusted HR=3.26, 95% CI 1.65-6.45, p=.001) and overall mortality (adjusted HR=2.28, 95% CI 1.22-4.27, p=.01). AKI is a frequent complication after CBT and is associated with worse outcomes. Questions remain as to the mechanism of the protective role of steroids on kidney function in the setting of CBT.